Kilasah Village Development is Based on Local Entrepreneurship with Small Capital - Purbohastuti, Arum Wahyuni; Mahardika, Mustafidah; Pertiwi, Widya Nur Bhakti; Kusyanto, Muhammad Johan Widi; Lusianingrum, Farah Putri Wenang (MOVE: Journal of Community Service and Engagement, 2026)
One important approach to encouraging local economic growth and improving public health is the development of village-based entrepreneurship. Kilasah Village, Serang Regency, has both natural and human resources, but these are not yet well-managed. The goal of this mentoring program is to foster entrepreneurship in Kilasah Village by employing a community empowerment approach, enhancing the capabilities of business actors, and harnessing local potential. Methods used include interviews with village officials and the community, implementing an entrepreneurship mentoring program, and field observations. The results show that developing entrepreneurship in Kilasah Village can attract more people and increase residents' incomes. However, several obstacles exist, such as limited capital, marketing, and business management. Therefore, to maintain village entrepreneurship, the village government, academics, and the community must work together continuously.